HEALTH AND HIGIENE AS ELEMENTS IN THE CONSTITUTION OF THE SCHOOL CULTURE FROM THE PERSPECTIVE OF EDUCAÇÃO PHYSICA MAGAZINE (Fiep Bulletin - online, 2014)
Abstract: This work analyses the ideas published in the articles of Physical Education, a magazine that was published from 1932 to 1945. We limited ourselves to the discussions about health and hygiene, once they were showed as primary issues by the scholars that wrote in the magazine. The articles were analyzed in order to detect their role in the constitution of a school culture, starting from children's education on. As references, we have taken Julias'reflections (2001) that limit and articulate the concept of school culture, taking them as elements that allow us to understand the set of principles that define the content to be taught, the behavior to internalize, and the set of practices that allow the circulation of such knowledge, as well as the incorporation of these behaviors, rules and coordinated practices to the purposes that may vary according to time and context. The study points to the comprehension of the historical aspect of the educational culture, not as something neutral or inert, but as something that is in constant movement and change. Children's schooling / education took place following proposals for health and hygiene. The physical education was viewed as an instrument that could reflect the ideal of a national education focused on the body, emphasizing a bio-psycho-social preparation for the modernity. The schooling culture of the period was born from a yearning for an economic order, but didn't stop there. The representations related to the school education focused by the magazine lead to the ways by which a group tries to be politically recognized in order to determine which skills and practices should make up the repertoire elicited by Physical Education teachers in their teaching practice.
Keywords: Physical Education; childhood; schooling culture